2022
DOI: 10.7554/elife.70207
|View full text |Cite
|
Sign up to set email alerts
|

Widespread discrepancy in Nnt genotypes and genetic backgrounds complicates granzyme A and other knockout mouse studies

Abstract: Granzyme A (GZMA) is a serine protease secreted by cytotoxic lymphocytes, with Gzma-/- mouse studies having informed our understanding of GZMA’s physiological function. We show herein that Gzma-/- mice have a mixed C57BL/6J and C57BL/6N genetic background and retain the full-length nicotinamide nucleotide transhydrogenase (Nnt) gene, whereas Nnt is truncated in C57BL/6J mice. Chikungunya viral arthritis was substantially ameliorated in Gzma-/- mice; however, the presence of Nnt and the C57BL/6N background, rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 151 publications
4
32
0
Order By: Relevance
“…The genetic background can thus influence SARS-CoV-2 induced inflammatory immunopathology in the K18-hACE2 model (Table 2); an observation consistent with a previous report that showed such a mixed background can also significantly affect an arthritic inflammatory immunopathology (52). The Nnt gene may, at least in part, be responsible as NNT controls mitochondrial reactive oxygen species via the glutathione and thioredoxin pathways, and thus generally exerts an anti-inflammatory influence (52). No significant differences in tissues titres were observed (Figure 5E), consistent with previous studies which also showed no detectable influence of such a mixed background on antiviral activity against an alphavirus (52).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The genetic background can thus influence SARS-CoV-2 induced inflammatory immunopathology in the K18-hACE2 model (Table 2); an observation consistent with a previous report that showed such a mixed background can also significantly affect an arthritic inflammatory immunopathology (52). The Nnt gene may, at least in part, be responsible as NNT controls mitochondrial reactive oxygen species via the glutathione and thioredoxin pathways, and thus generally exerts an anti-inflammatory influence (52). No significant differences in tissues titres were observed (Figure 5E), consistent with previous studies which also showed no detectable influence of such a mixed background on antiviral activity against an alphavirus (52).…”
Section: Resultssupporting
confidence: 89%
“…Weight loss, disease scores and survival were all significantly worse in K18-hACE2 6J mice than in the K18-hACE2 6N/6J mice (Figure 5B-D). The genetic background can thus influence SARS-CoV-2 induced inflammatory immunopathology in the K18-hACE2 model (Table 2); an observation consistent with a previous report that showed such a mixed background can also significantly affect an arthritic inflammatory immunopathology (52). The Nnt gene may, at least in part, be responsible as NNT controls mitochondrial reactive oxygen species via the glutathione and thioredoxin pathways, and thus generally exerts an anti-inflammatory influence (52).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations